ASPECTS INFLUENCING PERONAL HEALTH AND LIFE INSURANCE PURCHASE: INSURANCE AGENTS AND CUSTOMERSâ VIEW - Matthew Sanjaya, Steve
Health and life insurance is one of the most important aspects to consider in financial planning. It can help provide the fastest and most efficient way to prepare emergency funds for health and death risks. Although the insurance industry in Indonesia continues to grow and sales continue to rise, the data shows that Indonesia's insurance penetration and density are lower than the neighboring countries in ASEAN, where penetration is only at 1.7% compared to 5.3%, 2%, and 3% in Malaysia, Philippines, and Vietnam respectively in 2021. The overall insurance industry also has a bad reputation due to many frauds and scandals involving insurance. This study aims to identify the aspects that can influence the purchase of personal life & health insurance and how those factors influence the purchase decision. With this understanding, insurance marketers can adjust how they conduct selling practices and, therefore, can increase insurance selling. An interview was conducted with 17 respondents from different demographic groups and covered those who have bought and haven't bought insurance.